Reflection paper on MRSA in food-producing and companion animals: epidemiology and control options for human and animal health - Boudewijn Catry; Engeline van Duijkeren; Constança Pomba; Christina Greko; Miguel Á. Moreno; Satu Pyörälä; Modestas Ružauskas; Pascal Sandérs; E. J. Threlfall; F. R. Ungemach; Karolina Törneke; C. MUŇOZ-MADERO; et al. (2010)
SUMMARY The scope of this reflection paper was to review the latest research on the risk of MRSA infection and colonization in animals. Attention focused on occurrence, risk factors for colonization and infection, and human contact hazard for livestock, horses, and companion animals. Whereas the clonal relationship between MRSA strains of CC398 is straightforward in livestock this is less obvious in horses. Small companion animals typically share MRSA strains that seem to exchange with a human reservoir. Management and therapeutic options have been suggested for livestock, horses, companion animals, as well as instructions on safety measures for persons in contact with animals. Conclusions were drawn with emphasis on future research activities, especially to confirm the apparent evolution of the organism and to demonstrate efficiency of control strategies.